2005
DOI: 10.1095/biolreprod.105.044727
|View full text |Cite
|
Sign up to set email alerts
|

Promoter-Specific Expression of the Imprinted IGF2 Gene in Cattle (Bos taurus)1

Abstract: The domestic cattle (Bos taurus) has been a good animal model for embryo biotechnologies, such as in vitro fertilization and nuclear transfer. However, animals produced from these technologies often suffer from large-calf syndrome, suggesting fetal growth disregulation. The product of the insulin-like growth factor 2 (IGF2) gene is one of the most important fetal mitogens known to date. A detailed analysis of age-, tissue-, and allele-specific expression of IGF2 has not been performed in the bovine mainly beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
38
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 28 publications
7
38
0
1
Order By: Relevance
“…In the liver of a male foetus from 2-month gestation the paternal allele was primarily expressed, as shown by both cDNA sequencing and PCR-RFLP. Therefore, in agreement with the previously reported data (Curchoe et al, 2005), our results showed that in bovine liver the paternal allele-specific expression of the IGF2 gene occurred only in early stages of development, i.e. in foetuses up to two months of gestation.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…In the liver of a male foetus from 2-month gestation the paternal allele was primarily expressed, as shown by both cDNA sequencing and PCR-RFLP. Therefore, in agreement with the previously reported data (Curchoe et al, 2005), our results showed that in bovine liver the paternal allele-specific expression of the IGF2 gene occurred only in early stages of development, i.e. in foetuses up to two months of gestation.…”
Section: Resultssupporting
confidence: 93%
“…Total RNA was isolated from livers of heterozygous CT bulls, reverse transcribed to cDNA, and PCR amplified using primers matching exon 2, with the polymorphic g.292C>T site. These primers allowed the identification of liver-specific IGF2 mRNA, transcribed from IGF2 promoter 1 (bovine IGF2 gene has four alternative promoters -P1, P2, P3, and P4; Curchoe et al, 2005). Previously, while studying the IGF2 gene expression in different organs/tissues of adult, 15-months-old HF bulls by real-time PCR we found a relatively high content of IGF2 mRNA in kidney, liver and testis, but only trace amounts in bovine muscles (longissimus dorsi and semitendinosus) (Lisowski and Zwierzchowski, unpublished).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preferential paternal expression of the IGF-II gene was first reported by Dindot et al (2004). In addition, Curchoe et al (2005) showed a promoter-specific loss of imprinting of the IGF-II gene in cattle after birth.…”
Section: Introductionmentioning
confidence: 87%
“…Curchoe et al (2005) identified an SNP in exon 3 and an SNP after the stop codon of exon 10, and an indel in IGF-II of Bos taurus was reported by Flisikowski et al (2006). A C/T transition (RFLP-BsrI) at position 292 was first reported by Goodall and Schmutz (2003).…”
Section: Introductionmentioning
confidence: 94%